(untitled) (Bangladesh Pharmaceutical Journal, 2021)
As there is a resurgence of interest in plants as promising sources of new active pharmaceutical constituents, the present study has been designed to establish the preliminary biological activities of Blumea clarkei Hook.f. leaves. Here, the crude methanol extract of the leaves along with its organic and aqueous soluble fractions were subjected to different in vitro and in vivo assays. The ethyl acetate soluble fraction exhibited the highest total phenolic content (71.59 mg of GAE/gm of extract) and DPPH free radical scavenging (IC50 value 19.25 μg/ml) whereas another polar fraction; the aqueous soluble extractive showed the maximum cytotoxicity (LC50 value of 18.60 μg/ml) in the brine shrimp lethality assay. In membrane stabilizing activity evaluation, the inhibition of hypotonic solution and heat induced hemolysis were revealed maximum by the DCM (30.64%) and aqueous soluble fraction (39.15%), respectively while the crude methanol extract exhibited the highest thrombolytic potential (30.47% clot lysis). The central analgesic activity of the crude extract significantly increased the latent response time in tail-immersion method (p<0.001) at doses 200 and 400 mg/kg of body weight after 90 minutes of administration when compared to the control group. In acetic acid-induced writhing method, the plant extract showed prominent peripheral analgesia (p<0.001) with 47.54% and 65.57% inhibition at 200- and 400-mg/kg of body weight, respectively. In addition, a dose dependent hypoglycemic and antidiarrheal activities were also observed by the crude extract. Bangladesh Pharmaceutical Journal 24(2): 149-158, 2021